Kecenderungan Pola Asuh Permisif dan Kepercayaan Diri dengan Motivasi Berprestasi pada Siswa - Fatwati, Annisa Mentari; Fakhruddiana, Fuadah (Universitas Ahmad Dahlan, 2014)
ABSTRACTThis research was intended to find out the correlation of the tend to permissiveness parenting, self-confidence, and achievement motivation. The subjects were 61 students of VII Class of Junior High School. This research used quantitative method. Data were collected through Achievement Motivation Scale, Scale of Tend to Permissiveness Parenting Style Perception, and Scale of Self-Confidence. Regression analysis and partial correlation were used as analysis techniques.The results showed that there was correlation between tend to permissiveness parenting style and self-confidence to achievement motivation with R value =. 0,588, p = 0,000 (p < 0,01). The contribution from two variables to achievement motivation were 34,5 %. The partial correlation showed that there was a negative correlation between permissiveness parenting with achievement motivation and a positive correlation between self-confidence with achievement motivation on students. This research was concluded that there is a very significant correlation between the tend to permissiveness parenting, self-confidence, and achievement motivation on students.Keywords: achievement motivation, self-confidence, tend to permissiveness parenting,